SYNTHESIS OF TRANSPARENT POROUS MATERIAL AS DUST FILTER - CITRA DEWI (NIM: 20214002), YUNITA
The research of synthesis transparent porous material as dust filter has been done. The dust filter that has been made is expected to be applied on face mask to protect human respiratory system from hazardous airbones. At the time of Ihram activities, the pilgrims are encouraged to reveal his face for some reason. The use of masks by the pilgrims is needed, especially during and after a sand storm. Transparent mask is expected to be a solution for these problems. Based on this background, the aim of this research is to search for material composition and suitable method in making transparent mask. It is hoped unbreakable and having enough porousity to filter dust particle in the airbone. Selection of filter material constituted by the filter structure which normally form fiber structure with a small diameter. Biocellulose fiber of nata de coco have a diameter in nanometer scale and it is soft texture, strong, and transparent. Experimental methods starting from making a hole in the plastic then making, drying, grinding until coating nata de coco on the substrate like tulle cotton, nylon mesh and the outer layer of mask. Characterization of samples includes SEM test, transparency and filtration test. The best sample selected is a sample that uses nylon mesh substrate and the outermost layer of ordinary surgical masks. Both of the substrate is coated by the mill nata de coco by means of dip coating then drying under the sun. Highest surface porosity of the samples is 46%. The highest transparency achieved by the samples that using nylon mesh substrate. The sample value transparency is 69.57%. Based on filtration test, the pressure drop of the sample with nylon mesh substrate and the outer layers of mask substrate were respectively 45.69 Pa and 119.23 Pa. These value are smaller than pressure drop value of regular surgical masks. Besides of that, the value of maximum filtration efficiency at 2 m aerosol size is achieved by the sample that using outermost layer mask substrate, that is 44.44%. Based on the analysis of quality factor (QF) filtration test, the best quality of the sample is dipcoating nata de coco on the substrate nylon mesh sample with QF value on 8 x 10-3.